Poppers retinopathy. (7th March 2016) - Luis, Joshua; Virdi, Meena; Nabili, Shahriar
Abstract : We present a case of a 52-year-old man with sudden, bilateral central loss of vision as a result of inhalation of 'poppers'. He was found to have characteristic changes on optical coherence tomography. With conservative treatment, the patient's vision improved marginally at 3 months follow-up. An overview of previous published cases is also included.